1991
DOI: 10.4319/lo.1991.36.2.0315
|View full text |Cite
|
Sign up to set email alerts
|

Biological availability of dissolved organic carbon along the Ogeechee River

Abstract: Quality of dissolved organic C (DOC) from main‐stem and tributary sites along the Ogeechee River was compared to that of chemically defined organic C substrates in terms of biological availability. Availability was determined by measuring bacterial growth on natural river water (collected at high and low discharges) and defined organic substrates (humic standards and high‐quality sources of C). Availability of DOC to the natural (native) stream bacterial assemblage was compared to that of a defined bacterial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 15 publications
8
79
3
Order By: Relevance
“…However, we do acknowledge, that these filters do not necessarily remove all bacterivores and that a small number could have remained in the inoculum. Although some have argued strongly that in such studies, the use of a ''defined'' microbial inocula is warranted in order to provide an absolute measure of DOC quality (Leff and Meyer 1991), the use of a native assemblage in this study was justified. As we were working with fresh and saline water, it would have been impossible to develop a defined inocula which would grow in both systems.…”
Section: Methodsmentioning
confidence: 99%
“…However, we do acknowledge, that these filters do not necessarily remove all bacterivores and that a small number could have remained in the inoculum. Although some have argued strongly that in such studies, the use of a ''defined'' microbial inocula is warranted in order to provide an absolute measure of DOC quality (Leff and Meyer 1991), the use of a native assemblage in this study was justified. As we were working with fresh and saline water, it would have been impossible to develop a defined inocula which would grow in both systems.…”
Section: Methodsmentioning
confidence: 99%
“…Buffam et al (2001) for example showed in freshwater streams that storm flow, whilst only occurring for a fraction of the time compared to base flow, accounted for over half the annual DOC load. Wiegner et al (2009) and Leff and Meyer (1991) have shown that the bioavailability of DOC to heterotrophic bacteria can change between storm and base flow conditions. Our separation of storm flows into flood, fresh and base flow categories here has proven useful as a simple way of understanding how variable hydrological conditions may structure carbon dynamics.…”
Section: 5)mentioning
confidence: 99%
“…They are second-to third-order streams with different vegetation types, located in different regions of the USA. The streams are as follows: Meyers Branch, located on the Savannah River Site near Aiken, South Carolina a blackwater stream with dense vegetation dominated by cypress, tupelo, maple, hickory, willow, and birch [9]; Black Creek, another blackwater stream, on the lower coastal plain of Georgia with cypress-dominated floodplains [15] [7]; and the West Branch of the Mahoning River located within Jenning's Woods in Portage County, Ohio [13], a highly shaded stream with riparian vegetation that includes oak, maple, sycamore, and poplar.…”
Section: Study Sites and Sample Collectionmentioning
confidence: 99%
“…Several studies have reported dynamic changes, both spatially, within a watershed, and temporally, in the abundance and distribution of selected stream bacterial populations [11,12,[14][15][16][17]19]. However, differences in stream bacterial populations among watersheds from diverse regions exhibiting differing environmental conditions have not been examined [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation